Activin A more prominently regulates muscle mass in primates than does GDF8 - Esther Latres (Nature Portfolio, 2017)
Inhibition of GDF8 increases muscle mass in mice, but is less effective in monkeys and humans. Here the authors show that activin A also inhibits muscle hypertrophy and that concomitant inhibition of activin A and GDF8 synergistically increases muscle mass in mice and non-human primates.